Implications of Hasad Traits in Student Character Education at Alwashliyah University - Nur Azizah Nasution; Laila Auni (Edumaspul: Jurnal Pendidikan, 2023)
The aim of this research is to determine the implications of the nature of evil on student character education. The purpose of Allah SWT forbidding someone from having this inner attitude is none other than to educate and develop humans themselves so that they become people who can build good relationships with Allah and with fellow humans. Islam wants human life to be in harmony with God, with each other, and with the natural environment. The results of this research show that the impact or consequences of hasad do not only affect the person who is the object of the act, but also the perpetrator. There are several forms of impact of this hasad on the perpetrators.